Collaborative Writing Models for Enhancing Academic Publication Productivity: A Systematic Literature Review - Pance Daniel; Umi Narimawati; Bobi Kurniawan (Journal of General Education and Humanities, 2026)
Increasing publication pressure in academia has prompted universities and research institutions to adopt strategies to improve scholarly productivity and research competitiveness. The demand for measurable research performance, reflected through publication output, citations, and international visibility, has led institutions to explore collaborative approaches to academic writing. This study aims to analyze collaborative writing models that can improve academic publication productivity in higher education institutions. The research employed a systematic literature review (SLR) method to synthesize empirical evidence from previous studies. Data were collected from 25 empirical research articles published between 2015 and 2025 in reputable academic databases. The selected studies were analyzed using thematic synthesis to identify patterns, structures, and outcomes of collaborative writing practices in academic environments. The findings reveal four main collaborative mechanisms that significantly contribute to publication productivity: structured role allocation within writing teams, integration of digital collaboration technologies, mentoring-based writing systems, and interdisciplinary research collaboration. These mechanisms collectively enhance manuscript completion rates, improve publication quality, and increase research visibility. The results indicate that collaborative writing is not merely a shared authorship activity but a strategic organizational approach to strengthening research capacity. The study implies that academic institutions should institutionalize structured collaborative writing programs, provide digital infrastructure, and establish mentoring systems to sustainably improve publication output and global research competitiveness